La ilustración digital como aspecto cultural dentro de lo estético y comunicativo de la medicina ancestral andina en la ciudad de Latacunga. - Ríos Delgado, Naomy Alexia (2023)
The loss of knowledge within ancestral medicine is due to modernization, social, economic and cultural changes, as a consequence it has declined for the Taitas and Mamas, who used to conduct rituals and ceremonies in order to heal spiritual, physic and mental diseases. Those procedures were carried out during several years among the families of Latacunga, being for some of them, their main source of income. The goal of the research was to design a graphic product by the use of digital illustration as a cultural aspect within aesthetics and communication of Andean ancestral medicine in Latacunga city. Bruce Archer’s methodology was taken as reference, composed by three phases: first, the analytical process, in which, primary and secondary information was selected, then the creative phase, for this, several sketches were drawn in a field journal as part of the creative process to create the visual product. Lastly, the executive phase that allowed to make some procedures in order shape up the final result. Field research was performed altogether with documental review to subsequently analyze and interpret the graphic and academic data. The final asset was an art book containing the visual narrative of the approach to the Taita for a spiritual healing ritual, on the other hand, it also includes the depiction of the characters, the chakras, furthermore, there is illustrated information about the plants used and its role in the ceremony. To conclude it can be highlighted the relevance of ancestral medicine and the traditions transmitted from one generation to the next as an intangible legacy and cultural identity as part of our roots. This research was made as a contribution to the 5200 members of the foundation FHYMMATTAC (Taitas y Mamas del Ecuador) a social, cultural and scientific foundation of spiritual leaders, wise men and women who have knowledge and practice Ancestral and Spiritual Medicine.